Dialektika Agama: Harmoni dalam Jemaat Ahmadiyah Studi Living Qur’ān dan Konstruksi Damai di Kelurahan Gondrong Kenanga Tangerang Banten - Adrika Fithrotul Aini (Refleksi, 2015)
Within vast intolerant attitudes toward Jemaat Ahmadiyah, thecommunity at Gondrong Kenanga, Tangerang, Banten, appears to respectand highly support dissimilarity. Gondrong Kenanga is a place where manyreligious people reside, such as Ahmadiyah, NU, Muhamadiyah and others.They live together without conflict, but in harmony and peaceful condition.This article will discribe a concept of peace belonging to Ahmadiyah atGondrong Kenanga, in which it bases on the Qur’ānic doctrine that relatedto pluralism and harmony.